Respuesta :
Equation 1) 3x + 3y = 12
Equation 2) x - 5y = 10
First step : 3(x - 5y = 10)
Well, we have to simplify this equation first. *Remember, this is the second equation.
Equation 1) 3x + 3y = 12
Equation 2) 3x - 14y = 30
Well, because both equation 1 & 2 have positive 3x in their equations, we must subtract the equations from one another in order to find the y value.
So, your answer is : C) Subtract the equations.
~Hope I helped!~
Equation 2) x - 5y = 10
First step : 3(x - 5y = 10)
Well, we have to simplify this equation first. *Remember, this is the second equation.
Equation 1) 3x + 3y = 12
Equation 2) 3x - 14y = 30
Well, because both equation 1 & 2 have positive 3x in their equations, we must subtract the equations from one another in order to find the y value.
So, your answer is : C) Subtract the equations.
~Hope I helped!~